(untitled) (Research, Society and Development, 2024)
The objective of this study was to analyze the evaluation practices implemented by teachers in the development of teaching and learning of the 8th Grades of Elementary School of a state public school in the Municipality of Boa Vista – Roraima – Brazil, from 2008 to 2010. knowing the opinions of teachers and students. Considering the problem: does the assessment practice in the learning assessment process occur appropriately in relation to the comprehensive view of students’ potential? It was a qualitative-quantitative research, Hermeneutic method, through Content Analysis, based on reading, analysis and interpretation of data. Target population of 125 students and 50 teachers and a sample of 50 students and 10 teachers, with questionnaires with open and closed questions. As results, we can highlight the importance of the contributions of assessment and its influence on the teaching and learning process, since its role in this process is perceived and understood, with students and teachers as the main actors. The relevance of continued training and improvement of the teaching and learning process is also addressed, identification of the function of assessment in the school context, characterizing the type of assessment practiced in the school and its concept and its influence on the teaching and learning process. Thus, we seek a contribution to a reflection by managers and students on the evaluation process adopted by the school and carried out by teachers, observing questions about the evaluation of learning, clarifying and understanding that the evaluation act is aimed at both the student and the the teacher.